The transporter ABCB7 is a mediator of the phenotype of acquired refractory anemia with ring sideroblasts. - Nikpour, M; Scharenberg, C; Liu, A; Conte, S; Karimi, M; Mortera-Blanco, T; Giai, V; Fernandez-Mercado, M; Papaemmanuil, E; Högstrand, K; Jansson, M; Vedin, I; et al. (2013)
Refractory anemia with ring sideroblasts (RARS) is characterized by mitochondrial ferritin (FTMT) accumulation and markedly suppressed expression of the iron transporter ABCB7. To test the hypothesis that ABCB7 is a key mediator of ineffective erythropoiesis of RARS, we modulated its expression in hematopoietic cells. ABCB7 up and downregulation did not influence growth and survival of K562 cells. In normal bone marrow, ABCB7 downregulation reduced erythroid differentiation, growth and colony formation, and resulted in a gene expression pattern similar to that observed in intermediate RARS erythroblasts, and in the accumulation of FTMT. Importantly, forced ABCB7 expression restored erythroid colony growth and decreased FTMT expression level in RARS CD34+ marrow cells. Mutations in the SF3B1 gene, a core component of the RNA splicing machinery, were recently identified in a high proportion of patients with RARS and 11 of the 13 RARS patients in this study carried this mutation. Interestingly, ABCB7 exon usage differed between normal bone marrow and RARS, as well as within the RARS cohort. In addition, SF3B1 silencing resulted in downregulation of ABCB7 in K562 cells undergoing erythroid differentiation. Our findings support that ABCB7 is implicated in the phenotype of acquired RARS and suggest a relation between SF3B1 mutations and ABCB7 downregulation.